2022
DOI: 10.1021/acs.jpcb.2c05321
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Sequence: Internucleosomal Interactions Dominate Array Assembly

Abstract: The organization of the nucleosome array is a critical component of the chromatin assembly into higher order structure as well as its function. Here, we investigated the contributions of the DNA sequence and internucleosomal interactions on the organization of the nucleosomal arrays in compact structures using atomic force microscopy. We assembled nucleosomes on DNA substrates allowing for the formation of tetranucleosomes. We found that nucleosomes are capable of close positioning with no discernible space be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…2), the nucleosome can be seen to be overwrapped. These data show that there was a partial unwrapping event that started in frame (11) and proceeded to frame (13), where the nucleosome went from a state of overwrapped (~210 bp) and, throughout three frames, it decreased to an under wrapped state (~100 bp), where it remained bound for another 7 frames. The last frame 29 shows the nucleosome wholly disassociated from the DNA.…”
Section: A Step-wise Nucleosomes Unravelingmentioning
confidence: 83%
See 2 more Smart Citations
“…2), the nucleosome can be seen to be overwrapped. These data show that there was a partial unwrapping event that started in frame (11) and proceeded to frame (13), where the nucleosome went from a state of overwrapped (~210 bp) and, throughout three frames, it decreased to an under wrapped state (~100 bp), where it remained bound for another 7 frames. The last frame 29 shows the nucleosome wholly disassociated from the DNA.…”
Section: A Step-wise Nucleosomes Unravelingmentioning
confidence: 83%
“…We have demonstrated that the balance between energies of internucleosomal interaction and the affinity of the nucleosome core to the DNA sequence previously defines the formation of tight contacts between the nucleosomes. 10,13 The balance favors the dinucleosome assembly for non-specific DNA sequences. We have shown that the number of such contacts increases in nucleosomes assembled with truncated H4 histone, suggesting that histone tails contribute to the tightening of dinucleosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated stability of the nucleosome assembled by the specific 601 DNA sequence can explain this effect 37 . Still, we need to consider the difference in the interaction of NF-κB with both DNA templates.…”
Section: Discussionmentioning
confidence: 99%
“…However, nucleosomes were assembled on the highly specific 601 sequence in that publication, and a lower unwrapping effect was observed. Elevated stability of the nucleosome assembled by the specific 601 DNA sequence can explain this effect 37 . Still, we need to consider the difference in the interaction of NF-κB with both DNA templates.…”
Section: Discussionmentioning
confidence: 99%